Donepezil markedly prevents the progression of chronic heart failure and renal dysfunction in renal artery stenosis-induced hypertensive rats. (25th November 2020) - Li, M; Zheng, C; Kawada, T; Uemura, K; Inagaki, M; Nishikawa, T; Sugimachi, M
Abstract: Introduction: Parasympathetic activation by donepezil has been shown to improve prognosis in chronic heart failure (CHF) rats following myocardial infarction. We examined whether donepezil is effective in the treatment of another CHF model complicated with renal artery stenosis (RAS)-induced hypertension. Methods: RAS was created by ligating the left renal artery up to 50% in SD rats, at the same time, we implanted a blood pressure (BP) transmitter for confirming RAS-induced hypertension (7-week post-RAS: systolic BP = 154±7 mmHg; diastolic BP = 115±8 mmHg). In the 11th week after induction of RAS, surviving animals were randomly assigned to untreated (UT, n=10) or donepezil treated [DT, n=10, dissolved in drinking water (3mg/kg/day)] group. After a 6-week treatment, the effects of donepezil were evaluated by hemodynamics, blood levels of neurohumoral markers, and morphology. Results: Compared with UT, DT significantly prevented the progression of the left kidney atrophy (2.38±0.13 vs. 1.51±0.34 g/kg, P<0.05) and kidney fibrosis (left: −64%, P<0.001; right: −55%, P<0.01). DT also significantly prevented the progression of CHF, through suppressing cardiac hypertrophy (2.30±0.06 vs. 2.57±0.08 g/kg, P<0.01), cardiac fibrosis (−70%, P<0.01), and cardiac dysfunction [cardiac index: 102±3 vs. 86±3 ml/min/kg, P<0.05; left ventricular (LV) end-diastolic pressure: 12±2 vs. 20±2 mmHg, P<0.05; LV dp/dtmin: 5856±259 vs. 4924±227 mmHg/sec, P<0.05]. DT not only decreased serum levels of creatinine (0.54±0.02 vs. 0.63±0.03 mg/dl, P<0.05) and uric acid (1.4±0.2 vs. 1.9±0.2 mg/dl, P<0.05); but also decreased plasma levels of norepinephrine (273±38 vs. 846±242, P<0.01), AVP (2729±347 vs. 4783±695 pg/ml, P<0.05), BNP (360±13 vs. 460±39 pg/ml, P<0.05), angiotensin II and aldosteron, and suppressed the systemic inflammation. Conclusions: Donepezil treatment markedly prevented the progression of CHF and renal dysfunction, and improved the neurohumoral markers in the CHF rat model complicated with RAS-induced hypertension, suggesting that donepezil may be used as a new pharmacotherapy for CHF patients complicated with RAS-induced hypertension. Funding Acknowledgement: Type of funding source: None